An approach to building domain architectures using domain component model and architectural tactics. (1st January 2014) - Lee, Sung Nam; Ko, Deokyoon; Park, Sooyong; Kim, Suntae
In constructing software architecture, domain architecture is broadly adopted because it handles common functional requirements (FRs) and non-functional requirements (NFRs) and suggests both fundamental software structure and architectural strategy. In spite of the usefulness of the domain architecture, an approach to building domain architecture is carried out in an ad hoc manner. This paper presents an approach to building domain architecture by using domain requirements and architectural tactics. At first, application requirements are classified into domain FRs and NFRs, application specific FRs and NFRs. Then, domain components are derived from domain FRs, and architectural tactics are selected by using a quantitative approach to handle domain NFRs. Finally, domain architecture is produced after composing domain components and architectural tactic semantics. As all components are specified at UML meta-model level, it contains a feature that automatically instantiates application architectures in our proposed tool. This paper illustrates our approach by building the domain architecture of job candidate management to show feasibility of our approach.